Strategy for Increasing The Tourism Sector's Competitiveness in Increasing Regional Original Income at Buton Selatan Regency - Alauddin, La Ode Muhammad; Muhammad Yunus Amar; Darmawati, Darmawati (English and Tourism Studies, 2023)
South Buton Regency has extraordinary natural potential to attract tourists from various regions. However, the tourism potential of South Buton Regency has not been fully optimised because local revenue from the tourism sector is still relatively low, and its competitiveness also needs to be increased to compete with other tourism areas in Indonesia. This study aims to identify strategic factors, which are strengths and weaknesses as well as opportunities and threats, and then formulate strategic priorities to increase the tourism sector's competitiveness in increasing local revenue in South Buton Regency. The results of the study indicate alternative strategies that can be considered, including sustainable ecotourism, partnerships with the private sector, infrastructure improvement, development of training programs, diversification of tourism products, crisis management, reducing dependency and developing partnerships.